Internally Displaced Iraqi People in Kurdistan Urgently Need Global Heath Action: An Opportunity in Crisis - Maha Asham (Health for All Nations, 2015)
In January, 2014 Islamic State of Iraq and the Levant (ISIL) offensive on Iraq gave Christians, and other minorities a zero-sum ultimatum: convert to Islam, pay tax when ISIL ceased their assets, or get killed. Consequent massive waves of exudes displaced more than 2.5 million Iraqissheltered in 2,857 informal sites including 32 camps across Iraq creating the most rapidly unfolding humanitarian crisis in the world. More than 800,000 Iraqis sought refuge in Kurdistan region northern Iraq. Rising insurgent violence threatens 400,000 more displacements by December 2015.At present, the humanitarian caseload to 5.3 million people. The Chaldean Diocese assumed responsibility caring for tens of thousands displaced Iraqis flooding the city one June night, 2014. Today, the Chaldean Church is a lead humanitarian aid provider in and around Erbil having established and cares for 26 displacement centers and locations on ad-hoc basis. While international humanitarian assistance made its way to the region, IDP who reach relatively safe areas are largely neglected. The provision of essential public health services have sharply deteriorated. Health care and humanitarian relief in the region face three important challenges: mental and physical health issues imposed by atrocities of contemporary conflict, lack of data-driven assessment and reporting overshadowing persecuted Christians, and the neglect of victims especially those escaped ISIL captivity. Global health platforms have an awesome responsibility still sitting on back burners. Suffering 5.3 Iraqis deserve honest competent advocates and players to bring their situation live to the world. God empowers and calls the Christian Global Health and Medical community to respond (2Cor 1:7-11 NIV).